Anti-Science Politics and The Leadership Crisis in Handling The Covid-19 Pandemic in Indonesia - Mahpudin Mahpudin (Universitas Sultan Ageng Tirtayasa, 2024)
Anti-science has become a socio-political phenomenon that spreads in various worlds. Politicians and citizens behave in refusing information from experts for various reasons. In the context of a pandemic, the government or citizens often show doubts and rejection of intellectuals about the Covid-19 virus. This article attempts to explain the anti-science attitude of the Indonesian government in handling the pandemic which has implications for the occurrence of a political leadership crisis. This research uses qualitative methods while collecting data through literature studies (secondary data) from various sources such as journals, books, online articles, and others. The results of the study reveal that the government's attitude that tends to be anti-science has led to the absence of the political decision-making process and the formulation of evidence-based policies. The implication is that the government is experiencing difficulties in dealing with the COVID-19 pandemic and has a negative impact on people's lives at large. The pandemic outbreak has shown the government's stutter in managing the country and its citizensAnti-science has become a socio-political phenomenon that spreads in various worlds. Politicians and citizens behave in refusing information from experts for various reasons. In the context of a pandemic, the government or citizens often show doubts and rejection of intellectuals about the Covid-19 virus. This article attempts to explain the anti-science attitude of the Indonesian government in handling the pandemic which has implications for the occurrence of a political leadership crisis. This research uses qualitative methods while collecting data through literature studies (secondary data) from various sources such as journals, books, online articles, and others. The results of the study reveal that the government's attitude that tends to be anti-science has led to the absence of the political decision-making process and the formulation of evidence-based policies. The implication is that the government is experiencing difficulties in dealing with the COVID-19 pandemic and has a negative impact on people's lives at large. The pandemic outbreak has shown the government's stutter in managing the country and its citizens